Worldwide disparities in access to treatment and investigations for nephropathic cystinosis: a 2023 perspective - Regnier, Maitena; Flammier, Sacha; Boutaba, Mounia; Ndongo, Aliou Abdoulaye; Servais, Aude; Schaefer, Franz; Levtchenko, Elena; Bacchetta, Justine; Bertholet-Thomas, Aurélia (Pediatric nephrology, 2024)
Nephropathic cystinosis (NC) is a rare lysosomal disease, leading to early kidney failure and extra-renal comorbidities. Its prognosis strongly relies on early diagnosis and treatment by cysteamine. Developing economies (DEing) face many challenges when treating patients for rare and chronic diseases. The aim here is to evaluate the access to investigations and treatment in DEing, and to assess for potential inequalities with Developed Economies (DEed).
Online veröffentlicht am 18. November 2023
Gesehen am 11.03.2024